Observations on the Lysis of Artificial Thrombi by Urokinase - Ogston, C. M; Ogston, D; Fullerton, H. W (Thrombosis and Haemostasis, 1968)
1. The extent of lysis of artificial thrombi by urokinase is dependent on their fibrin content and on the plasminogen concentration of the plasma from which they are made.2. The lysis of thrombi in the presence of plasma increases with increasing concentrations of urokinase, but very high urokinase concentrations are inhibitory to thrombolysis.3. It is postulated that incomplete thrombolysis is due to insufficient plasmin formation within the thrombus, but that plasminogen-containing plasma can diffuse into a thrombus allowing lysis to continue until complete dissolution.